1678 A Rare Example of a Simple Bone Cyst of The Ascending Ramus in A Paediatric Patient. (12th October 2021) - Aruede, G; Carey, E; Bhatia, K; Smart, K
Abstract: A simple bone cyst is described as an intra-osseous pseudocyst, devoid of an epithelial lining and either empty of filled with serous or sanguineous fluid. This case presents a rare example of a simple bone cyst of the ascending ramus of the mandible in a paediatric patient. Studies have shown that less than 5% of simple bone cysts of the jaw bones are located within the mandibular ramus, with the most common site being the premolar-molar region (75%). The 14-year-old female was referred by her orthodontist to the local Oral and Maxillofacial department, for an incidental finding on her pre-orthodontic OPT of a radiolucency in the left ascending ramus. Her medical history was clear, she was asymptomatic and had no sensory deficit. A CT scan demonstrated a 22mm multilocular radiolucency centred on the left ascending ramus, extending superiorly up to the base of the coronoid process and condylar neck. Inferiorly, the radiolucency abutted but did not involve the unerupted third molar. The scan highlighted thinning of the buccal and lingual cortices putting the patient at risk of pathological fracture. The inferior alveolar nerve canal passed through the lingual aspect of the radiolucency. The patient underwent exploration of the left mandible which revealed an empty bony cavity, with no cystic lining or contents. The definitive diagnosis of a simple bone cyst was established. She experienced satisfactory healing by her review appointment 4 weeks post-surgery. Combined radiographic and clinical assessment is important in the diagnosis of simple bone cysts.